Evaluation of the knowledge on the special tax to the consumption in mototaxi’s operators of the canton St. Domingo, Ecuador - Calva Vega, Yolanda Guissell; Erazo Yépez, Milton Germán; Cañizares Galarza, Fredy Pablo; Montece Giler, Salomón Alejandro (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
The fond application of the tax to the Especial Consumptions to the sector of the mototaxis, without being sumptuous goods, on the contrary a tool and source are of work, that to for to be acquired the buyer pays this tax on the retail price suggested by the free will of importers or assemblers, since a regulations to fix it do not exist . The objective of investigation is based in evaluating the knowledge of the special tax to the consumption in mototaxi’s operators at the Canton St. Sunday, Ecuador. The design is qualitative quantitative, with a reach descriptico, the analytical synthetic, inductive deductive methods, historic logician, documentary, experts analysis, and the techniques of interview and opinion poll. The results indicate that they are ignorant of a mototaxistas’s loud percentage be more than enough the PULL UP which comes from for acquisition goods, imports, rendering of services.